Kdo izbira in kdo ponuja v izbiro? - Dolinar, Darko (Primerjalna književnost, 2010)
When faced with the question "Who chooses?" one usually thinks of readers facing a large corpus of highly diverse texts, trying to reconstruct, understand, or explain their internal mechanisms and selection procedures as well as external instances that are more or less involved. However, this selection takes place not only in the area covered by reception theory and reader-response criticism, but also, in various ways, throughout the entire literary communication cycle, from production to distribution and reception. This paper illustrates some key aspects of this issue, especially the intermediary function between supply and selection, by giving typical examples of Slovenian publishing and bookselling practices during recent decades and the "transition" into a capitalist market economy. It mainly focuses on examples that far exceed the average volume of reception and sales numbers.
Keywords: literarno posredništvo; založništvo; knjigotrštvo; uredniška politika; bralec; branje; literarni sistemi; knjižna selekcija